Identification of eight candidate target genes of the recurrent 3p12–p14 loss in cervical cancer by integrative genomic profiling. Issue 1 (14th March 2013) - Lando, Malin; Wilting, Saskia M; Snipstad, Kristin; Clancy, Trevor; Bierkens, Mariska; Aarnes, Eva‐Katrine; Holden, Marit; Stokke, Trond; Sundfør, Kolbein; Holm, Ruth; Kristensen, Gunnar B; Steenbergen, Renske DM; et al.
Abstract The pathogenetic role, including its target genes, of the recurrent 3p12–p14 loss in cervical cancer has remained unclear. To determine the onset of the event during carcinogenesis, we used microarray techniques and found that the loss was the most frequent 3p event, occurring in 61% of 92 invasive carcinomas, in only 2% of 43 high‐grade intraepithelial lesions (CIN2/3), and in 33% of 6 CIN3 lesions adjacent to invasive carcinomas, suggesting a role in acquisition of invasiveness or early during the invasive phase. We performed an integrative DNA copy number and expression analysis of 77 invasive carcinomas, where all genes within the recurrent region were included. We selected eight genes, THOC7, PSMD6, SLC25A26, TMF1, RYBP, SHQ1, EBLN2, and GBE1, which were highly down‐regulated in cases with loss, as confirmed at the protein level for RYBP and TMF1 by immunohistochemistry. The eight genes were subjected to network analysis based on the expression profiles, revealing interaction partners of proteins encoded by the genes that were coordinately regulated in tumours with loss. Several partners were shared among the eight genes, indicating crosstalk in their signalling. Gene ontology analysis showed enrichment of biological processes such as apoptosis, proliferation, and stress response in the network and suggested a relationship between down‐regulation of the eight genes and activation of tumourigenic pathways. Survival analysis showed prognostic impact of the eight‐gene signature that was confirmed in a validation cohort of 74 patients and was independent of clinical parameters. These results support the role of the eight candidate genes as targets of the 3p12–p14 loss in cervical cancer and suggest that the strong selection advantage of the loss during carcinogenesis might be caused by a synergetic effect of several tumourigenic processes controlled by these targets. Copyright © 2013 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.